(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge and practices regarding the prevention of urolithiasis among patients seeking outpatient care at Thu Duc General Hospital in 2025 and to identify related factors. Method: A descriptive cross-sectional study collected data through interviews using a validated questionnaire (Cronbach’s Alpha=0.84) on 400 individuals aged 18 years and older attending outpatient care at Thu Duc General Hospital, Ho Chi Minh City. Results: Overall knowledge about urolithiasis prevention was adequate in 35.5% of participants and inadequate in 64.5%; 29.0% demonstrated correct preventive practices while 71.0% did not. Factors associated with adequate knowledge included marital status (OR=2.6; 95% CI: 1.29-5.04; p=0.009) and educational level (OR=2.73; 95% CI: 1.23-4.91; p=0.006). Factors associated with correct practices included gender (OR=5.04; 95% CI: 3.0-8.46; p=0.03); marital status (OR=2.22; 95% CI: 1.16-4.26; p=0.01 and reason for hospital visit (OR=1.89; 95% CI: 1.08-3.42; p=0.03) Conclusion: The prevalence of adequate knowledge and correct practices regarding urolithiasis prevention remains low among study participants. Strengthening health communication and education is essential, including integrating urolithiasis prevention counseling into nephrology-urology examination protocols and using visual materials and short videos in waiting areas.